2014
DOI: 10.1095/biolreprod.114.122986
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone Receptor Membrane Component-1 (PGRMC1) and PGRMC-2 Interact to Suppress Entry into the Cell Cycle in Spontaneously Immortalized Rat Granulosa Cells1

Abstract: Progesterone receptor membrane component 1 (PGRMC1) and PGRMC2 are expressed in rat granulosa cells and spontaneously immortalized granulosa cells (SIGCs) but their biological roles are not well defined. The present studies demonstrate that depleting either Pgrmc1 or Pgrmc2 in SIGCs increases entry into the cell cycle but does not increase cell proliferation. Rather, PGRMC1 and/or PGRMC2-deplete cells accumulate in metaphase and undergo apoptosis. Because both PGRMC1 and PGRMC2 localize to the mitotic spindle,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
85
0
14

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(103 citation statements)
references
References 28 publications
(78 reference statements)
4
85
0
14
Order By: Relevance
“…This is consistent with effects of depleting PGRMC1 in SIGCs, where cells accumulate in metaphase and then undergo cell death. 12 Another possible outcome of cytokinesis failure is the formation of bior multi-nucleated cells. This is not the case for bGCs since multinucleated granulosa cells were not observed in PGRMC1 RNAi treated cells (data not shown).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with effects of depleting PGRMC1 in SIGCs, where cells accumulate in metaphase and then undergo cell death. 12 Another possible outcome of cytokinesis failure is the formation of bior multi-nucleated cells. This is not the case for bGCs since multinucleated granulosa cells were not observed in PGRMC1 RNAi treated cells (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…2,9 Accordingly, in vitro studies using different ovarian cell lines have shown that depleting PGRMC1 expression suppresses cell proliferation. [10][11][12] However the mechanism of action by which PGRMC1 controls ovarian cell proliferation is poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…41 More recently, PGRMC1 was shown to interact with PGRMC2 to suppress entry of SIGCs into the cell cycle. 42 During early gestation, PGRMC1 localizes to the nuclei of mitotic cells within the uterus at the interface between the undifferentiated and terminally differentiated stroma during decidualization. 43 A role for PGRMC1 in enhancing microtubule stability during mitosis has also been proposed, wherein PGRMC1 was found to directly interact with b-tubulin.…”
Section: Discussionmentioning
confidence: 99%
“…44 In addition to its role in metaphase, PGRMC1, along with its binding partner PGRMC2, is involved in regulating entry into the G1 stage of the granulosa cell cycle. 42,45 PGRMC1 forms a physical interaction with aurora kinase B on metaphase II chromosomes in bovine oocytes, and failure to do so is suggested to play a role in increased aneuploidy in cows with reduced antral follicle counts. 46 These studies in reproductive tissues provide foundational information about the mitotic/meiotic functions of PGRMC1 as a mediator of the actions of P4 in ovarian somatic and germ cells.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, this difference allows human PGRMC1 to form stable homodimers through hydrophobic heme-heme stacking interactions, explaining earlier observations of dimeric complexes (Min et al, 2004;Kabe et al, 2016). Since the hemebinding residues are conserved among MAPRs, these proteins may all share the ability of heme-dependent homo-and/or heterodimerization (Peluso et al, 2014). Although PGRMC1 had originally been defined as a component of a progesterone-binding protein complex with affinities in the nM range (Meyer et al, 1996), it remained questionable whether progesterone actually binds directly to PGRMC1 itself.…”
Section: Molecular Biochemical and Cellular Properties Of Maprsmentioning
confidence: 63%